Efeito da magnitude da perturbação na adaptação em uma tarefa de apontamento - Aline Horta Miguel (2012)
adaptation in an aiming task. Twenty volunteers (n=20), right-handed, college students, naive to the purpose of the experiment. They were divided into two groups which referred to the size of visuomotor perturbation: G30 (30º of rotation) e G60 (60º of rotation) took part in this study. The task apparatus consisted of a digitizing table, a digitizing pen, a computer and a wooden box covered with a cloth. The task required to make an aiming movement from one central dot to a specific target.There were two conditions: a) aiming to the right, from the central dot to the right target; b) aiming to the left, from the central dot to the left target. The targets appeared in a pseudo-random order. The experiment consisted of two phases: preexposition with 20 trials for each target and exposure with 80 trials for each target. In the exposure phase the visuomotor perturbation was manipulated. The trajectory was shown in the screen with 30º and 60º rotation counter-clockwise. The measures used in the experiment were the root mean square error (RMSE), movement time (TM), initial directional error at 100ms (IDE), zero line crossing acceleration (Nacel). Statistical tests were done with two-way ANOVA with Duncan's post hoc with significance level of p< 0,05 and an exponecial function was apllied to the RMSE exposure data. The exposition phase analysis showed that the time course of adaptation was different for the groups: G30 adapted faster than G60. There was no difference for the groups in the control mechanism during the exposition phase. Both groups used feedforward. However, the efficiency of the feedforward was influenced by the magnitude of perturbation. There was less efficiency for the bigger magnitude of the perturbation.